2018
DOI: 10.1155/2018/3708637
|View full text |Cite
|
Sign up to set email alerts
|

Chromium‐Containing Traditional Chinese Medicine, Tianmai Xiaoke Tablet, for Newly Diagnosed Type 2 Diabetes Mellitus: A Meta‐Analysis and Systematic Review of Randomized Clinical Trials

Abstract: Objective Chromium-containing traditional Chinese medicine Tianmai Xiaoke tablet (TMXKT) is approved for treating newly diagnosed type 2 diabetes mellitus (T2DM) in China. This review aimed to compile the evidence from randomized clinical trials (RCTs) and quantify the effects of TMXKT on newly diagnosed T2DM. MethodsSeven online databases were investigated up to March 20, 2017. The meta-analysis included RCTs investigating the treatment of newly diagnosed T2DM, in which TMXKT combined with conventional therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…Pharmacological investigations indicated that TCPMs present beneficial effects on reducing body weight, enhancing insulin sensitivity, protecting β-cells, improving insulin secretion, correcting glucose and lipid metabolism disorders, and improving the microcirculation and the immune system. [ 5 6 7 8 9 10 11 12 13 ] For example, the Tianmai Xiaoke tablet which contains of Schisandra Chinensis, Ophiopogon Japonicus, Trichosanthis Radix and Chromium Picolinate is approved by the State Food and Drug Administration of China (state medical license number Z20049007) can decrease FBG and HbA1c levels in T2DM patients. [26] In addition, some studies demonstrated that Tianmai Xiaoke tablets could down-regulate PTP1B and PCK2 by activating the insulin signaling pathway, thereby reducing the HbA1c level in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacological investigations indicated that TCPMs present beneficial effects on reducing body weight, enhancing insulin sensitivity, protecting β-cells, improving insulin secretion, correcting glucose and lipid metabolism disorders, and improving the microcirculation and the immune system. [ 5 6 7 8 9 10 11 12 13 ] For example, the Tianmai Xiaoke tablet which contains of Schisandra Chinensis, Ophiopogon Japonicus, Trichosanthis Radix and Chromium Picolinate is approved by the State Food and Drug Administration of China (state medical license number Z20049007) can decrease FBG and HbA1c levels in T2DM patients. [26] In addition, some studies demonstrated that Tianmai Xiaoke tablets could down-regulate PTP1B and PCK2 by activating the insulin signaling pathway, thereby reducing the HbA1c level in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 6 7 8 9 10 11 12 13 ] For example, the Tianmai Xiaoke tablet which contains of Schisandra Chinensis, Ophiopogon Japonicus, Trichosanthis Radix and Chromium Picolinate is approved by the State Food and Drug Administration of China (state medical license number Z20049007) can decrease FBG and HbA1c levels in T2DM patients. [26] In addition, some studies demonstrated that Tianmai Xiaoke tablets could down-regulate PTP1B and PCK2 by activating the insulin signaling pathway, thereby reducing the HbA1c level in diabetic rats. [27] Moreover, the Jinlida granule was verified that it could significantly improve glycemic control, alleviate insulin resistance, and promote insulin secretion, with greater improvements in patients with a long disease course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DM'nin en sık görülen türü olan Tip 2 DM'li hastalarla yapılan birçok çalışmada; diyabetli hastaların krom düzeylerinin, sağlıklı bireylere göre düşük olduğu sonucuna ulaşılmıştır [23,24]. Bu çalışmaların ışığında, Tip 2 DM'li hastalara tedavi amacıyla krom takviyesi verilmesi ile ilgili birçok çalışma yapılmıştır [25,26]. Tip 2 DM ve krom arasında ki ilişkiye yönelik yapılan bu çalışmalarda; krom düzeylerinin, Tip 2 DM'li hastalarda düşük olduğu ve krom takviyesinin de sınırlı bir etki ortaya koyduğu sonucuna ulaşılmıştır.…”
Section: Introductionunclassified
“…Cr not only acts as an antioxidant (23), but also involves the metabolism of carbohydrate, fat, and protein (24,25) and enables the activation of insulin and reduces fat deposits in the body (26). Cr is commonly used in the management of glucose and insulin metabolism by diabetic patients (27)(28)(29) and for muscle fatigue (30). Moreover, recent studies reported that Cr elevates insulin-stimulated glucose uptake in adipocytes (31) and cultured muscle cells (32).…”
Section: Introductionmentioning
confidence: 99%